Effects of Various Physical Education Curriculum on Motor Skills in Students of Final Grades in Primary School - Milovan Ljubojević; Aldijana Muratović; Marija Bubanja (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2016)
Results of many researches conducted in field of physical education show that the physical education curriculum is not on the appropriate and satisfactory level. The goal of this study is to determine effects of standard and experimental education curriculum on motor skills. This study lasted for one school year, and it was conducted on the sample consisting of 113 boys, divided into control (physical education) and experimental group (basketball). In order to asses motor space, following variables of Eurofit battery of tests were monitored: flamingo, hand tapping, seated forward bend (modified functional reach test), long jump, dynamo-metrics of dominant hand, lay - sit for 30'', pull-up endurance, and pin running on 10x5m. Analysis of the results during the final measurement showed that students of control group had better results in final measurement in comparison to the initial one in six out of eight variables. Students of the experimental group had improved results in 7 out of 8 variables. Experimental education curriculum with emphasize on basketball contributed to development of motor skills of students, but not at the level that would imply superiority over the control - standard education curriculum.